Potensi Suplemen Kerang Kijing (Pilsbryocomcha excilis) Sebagai Pupuk Alami Ramah Lingkungan: Potential of Mussel Shell (Pilsbryocomcha excilis) Suplement as Ecofertilizer - Irna Il Sanuriza; Dwi Kartika Risfianty (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
High input of chemical fertilizer causes land degradation on agriculture. This research is experimental which aims to analyze degree of acidity and macro-nutrients in mussel shell, and analyze chemical properties of soil before and after application of mussel shell suplement. The research was conducted during July to September 2020 at BPTP Laboratory, Narmada West Lombok. Data were analyzed descriptively. The results showed that mussel shell (Pilsbryocomcha excilis) had pH and macro-nutrients potential as an ecofertilizer. Soil chemical properties increase after application of mussel shell (Pilsbryocomcha excilis) supplement. Key words: mussel; shell; soil enhancer; suplement